Determinants of acceptance of the illness by hemodialysis patients - Łatka, Joanna; Majda, Anna; Sołtys, Agnieszka (Nursing Problems / Problemy Pielęgniarstwa, 2013)
Introduction. Treated hemodialysis patients with chronic renal failure in everyday life experience many of the restrictions and requirements on the part of the disease, which is, in many ways, difficult to accept. Aim of the study. The aim of the study was to diagnose the illness acceptance rate and understanding the role of socio- -demographic variables and variables specific to renal replacement therapy, and styles of coping with stress for the differentiation of the acceptance of the disease in patients with chronic renal failure undergoing hemodialysis. Material and methods. In the study 100 patients participated. The Acceptance of Illness Scale and Questionnaire Coping with Stressful Situations were used as well as own questionnaire which contained questions related to socio-demographic data and certain aspects of the disease and treatment. Results. Acceptance rate of the disease among the patients on hemodialysis was 22.76 (SD = 5.33). It has been shown a positive correlation between the level of acceptance of the disease and variables such as male gender, higher level of education, positive assessment of material situation, the feeling better between dialysis and its shorter total duration and also between coping style in patients with stress concentrated on the task or avoidance. Conclusions. The analysis of data from the study suggests the need to take into account the problem of acceptance of the disease by hemodialysis patients and occurrence of factors that differentiate in a positive or negative way the degree of acceptance of the disease at all stages of its duration.